Increasing Psychological Well-Being in Children with Chronic Illness through Social Support Intervention in Haji Adam Malik Hospital, Medan Tuntungan - Nasution, Indri Kemala; Daulay, Debby Anggraini; Siregar, Ade Rahmawati; Rangkuti, Rahmi Putri; Yurliani, Rahma; Marini, Liza (Journal of Saintech Transfer, 2018)
Chronic illness is a disorder/ disability due to medical conditions that are present continuously for 3 months or more which may affect the functioning of a child's life (Fritz & McQuaid in Wenar & Kerig, 2005). The effects of chronic illness and long-term treatment lead to individual psychological problems for children, such as feeling sad, withdrawing and other emotional problems. Poor psychological well-being conditions often exacerbate chronic childhood illness. Children become lazy to take medication and not obedient in doing treatment. The purpose of this devotion is to improve psychological well-being of children with chronic illness through social support interventions. This program will be carried out with a cadre of 3 partners who are nurses from Haji Adam Malik hospital. The nurses will be trained, so they can provide the social support for children during hospitalization to improve the psychological wellbeing of the children. After the training, social support interventions implementation module will be tested to 20 chronic illness children in Haji Adam Malik hospital with the nurse as a facilitator. While the team from Psychology Faculty will supervise the implementation and provide feedback.